VD_FINDINFO Arrêt / 2014 / 704 vom 11. Dezember 2014 - VD Tribunal cantonal (2014)
RESTITUTIONEN GÉNÉRAL, GAIN INTERMÉDIAIRE, SALAIRE USUEL, OBLIGATION DE RENSEIGNER | 95 al. 1 LACI, 25 LPGA, 27 LPGA, 53 LPGA